Development and validation of an LC–MS/MS method for the simultaneous quantification of seven constituents in rat plasma and application in a pharmacokinetic study of the Zaoren Anshen prescription. (24th August 2017) - Zhao, Ajing; Zhang, Li; Li, Rong; Shang, Jiao; Yi, Huihui; Wang, Yuan; Zhang, Dian; Wang, Shixiang; Fang, Minfeng
Abstract: A sensitive, specific and accurate liquid chromatography–tandem mass spectrometry (LC–MS/MS) method was developed and validated for the simultaneous determination of seven constituents of the Zaoren Anshen prescription (ZAP) in rat plasma after oral administration of the ZAP: spinosin, salvianic acid A, 6′′′‐feruloylspinosin, protocatechualdehyde, salvianolic acid B, schisandrin and deoxyschisandrin. The plasma samples and the internal standard (IS) sulfamethoxazole were extracted using acetonitrile. Chromatographic separation was performed with an Agilent HC‐C18 column using a gradient elution profile and a mobile phase consisting of 0.01% formic acid in water (A) and acetonitrile (B). The analytes were quantified simultaneously in a single run using an ion trap mass spectrometer operated in the multiple reaction monitoring mode and electrospray ion‐source polarity in the positive and negative modes. The calibration curves for spinosin, salvianic acid A, 6′′′‐feruloylspinosin, protocatechualdehyde, salvianolic acid B, schisandrin and deoxyschisandrin were linear over the concentration ranges of 2.90–1160, 2.50–1000, 1.80–720, 0.65–260, 2.50–1000, 8.00–1600 and 1.30–520 ng/mL, respectively. The intra‐ and inter‐day precisions in terms of relative standard deviation were <18.9%, and the accuracies in terms of relative error were within ±14.2%. Consequently, the proposed method was successfully applied to the pharmacokinetic analysis of these seven major active compounds in rats administered ZAP. These results will facilitate research aiming to predict the effectiveness of the optimal dose of ZAP and might be beneficial for the therapeutic use of ZAP in the clinical setting.